3 Laws of New Hampshire: Province Period 83 (Henry Harrison Metcalf ed., 1915) - (:unkn) unknown (My University, 1754)
Made the parents over persons under twenty-one liable for fines imposed for their sons' militia delinquency or neglect.
Keywords: MILITIAS